Effects of lipoteichoic and arachidonic acids on the immune-regulatory mechanism of bovine mammary epithelial cells using multi-omics analysis - Dong, Weitao; Chen, Yan; Zhang, Quanwei; Zhao, Xiaoxuan; Liu, Peiwen; He, Haijian; Lu, Ting; He, Yuxuan; Du, Xianghong; Hu, Junjie; Zhao, Xingxu; Zhang, Yong (Frontiers in Veterinary Science, 2022)
Staphylococcus aureus is one of the most important pathogens causing mastitis in dairy cows. It mainly utilizes the properties of its pathogenic factor, lipoteichoic acid (LTA), to elicit a host-cell inflammatory response and evade the host-cell immune response. Arachidonic acid (AA) has a regulatory role in the inflammatory response, cell metabolism, and apoptosis. The study aimed to establish a cell model by determining the optimal concentration of LTA and AA for cell induction using the Cell Counting Kit -8 assay and the quantitative polymerase chain reaction of interleukin (IL)-1β, IL-2, and IL-6. MAC-T cells were planted in 36 10-cm2 culture dishes at a density of 1×107 cells per dish. They were treated with LTA for 24 h to constitute the LTA group and with AA for 12 h to constitute the AA group. The cells were pretreated with LTA for 24 h followed by treatment with AA for 12 h to constitute the LTA+AA group. Using proteomic, transcriptomic, and metabolomic analyses, this study determined that LTA can regulate the expression of Actin Related protein 2/3 complex (ARPC)3, ARPC4, Charged Multivesicular Body Protein 3, protein kinase cGMP-dependent, NF-κB Inhibitor Alpha,and other genes to affect cellular metabolism, immune regulation and promote apoptosis. In contrast, AA was observed to regulate the expression of genes such as ARPC3, ARPC4, Charged Multivesicular Body Protein 3, Laminin Gamma 1, Insulin Receptor, Filamin B, and Casein Kinase 1 Epsilon to inhibit cellular apoptosis and promote immune regulation, which provides a theoretical basis for future studies.